2001
DOI: 10.1111/j.1545-5300.2001.4040100385.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heart of the Matter: An Essay about the Effects of Managed Care on Family Therapy with Children*

Abstract: This essay is based on a pilot study that examined the effects of managed care on the treatment of children and families, with special attention to community mental health. We embarked on the pilot study to test the accuracy and generalizability of our impression that family therapy and other systemic practices have been marginalized in ordinary clinics and agencies, and to understand the reasons why. We interviewed managed care providers, researchers, family therapy trainers, and clinicians in the Northeast. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…I will undertake both a personal and professional accounting of the interface of family therapy and frontline public sector practice. More than 10 years ago, Pulleyblank Coffey, Olson, and Sessions () documented the impact of managed care and other developments in public sector services on family therapy in community mental health centers. Based on interviews with managed care providers, researchers, family therapy trainers, and clinicians, they traced out intertwined trends of the medicalization of mental health, the rise of time consuming paperwork requirements, and funder reimbursement changes that encouraged agencies to move from salaried positions to “fee‐for‐service” positions in which clinicians are paid on an hourly basis for clients that they see.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I will undertake both a personal and professional accounting of the interface of family therapy and frontline public sector practice. More than 10 years ago, Pulleyblank Coffey, Olson, and Sessions () documented the impact of managed care and other developments in public sector services on family therapy in community mental health centers. Based on interviews with managed care providers, researchers, family therapy trainers, and clinicians, they traced out intertwined trends of the medicalization of mental health, the rise of time consuming paperwork requirements, and funder reimbursement changes that encouraged agencies to move from salaried positions to “fee‐for‐service” positions in which clinicians are paid on an hourly basis for clients that they see.…”
mentioning
confidence: 99%
“…So instead of me having a staff, I have a collection of entrepreneurs.” This trend contributed to greater isolation of clinicians, reduction in training in agencies, and encouragement of an atheoretical, primarily pragmatic approach to practice. Pulleyblank Coffee, Olson, and Sessions () concluded that family therapy's knowledge of human systems was in danger of being disqualified and lost with damaging consequences for the care of children. Since then, these trends have continued and have been exacerbated.…”
mentioning
confidence: 99%
“…These dilemmas highlight the tension between the therapist's agency and the power of the managed care system. Additionally, research has shown that structures requiring systemic therapists to use the language of managed care (i.e., medically oriented) results in loss of knowledge of systemic theories, reduced complexity in therapeutic family treatment, and increased focus on decontextualized biological explanations and practice (Pullyblank Coffey, Olson, & Sessions, ).…”
Section: Applying a Sociological Lens To Key Healthcare Structuresmentioning
confidence: 99%